The Study of Potential Medicinal Uses and Pharmacological Activity of Coccinea Grandis - Literature Review - Kugarani, M.; Sathiyaseelan, V. (Institute of Indigenous Medicine University of Colombo, Rajagiriya Sri Lanka, 2017)
Coccinea grandis belongs to family Cucurbitaceae, an ever green perennial climber with slender, cylindrical, glabrous stems and simple tendrils. Whole part of this plant use in traditional medicine. The objective of this study is to identify the medicinal uses and pharmacological activity of this plant. Leaves are applied on eruptions of skin such as ring worm, itch, psoriasis, leprosy, fever, asthma, bronchitis and jaundice. The plant taken internally as a decoction for gonorrhoea and diabetes. It is useful for dropsical conditions in acute and chronic pyelitis, cystitis and strangury. It has antilithic properties of some value and is largely employed for urinary gravel and calculi. The leaves are also cooked and eaten. The bark of the root has good cathartic action. The fruits and leaves are used in the treatment of snake-bite. Knowledge on medicinal uses of Coccinea grandis is not limited among Sri Lankan physicians. Data was gathered from Siddha and traditional medical books, journals and internet. Extract of the plant contains an enzyme involved in regulating sugar metabolism, a hormone and traces of an alkaloid. It has oxidizing property to oxidates followings Gypsum, Mankombu (Horn of the Deer), Silver and Stannum. Especially its leaves have pro vitamin A which is help to promote the vision. Its young pots also have folic acids which is help to promote the RBC maturation too. It has a wide range of actions, expectorant, antispasmodic, antiperiodic, cooling, diuretic and hypoglycemic.
Keywords: Coccinea grandis; Pharmocological activity; Medicinal uses